Specificities in the sectoral pattern of innovation in developing countries: an investigation for Brazilian industry - Milano de Lucena, Rodrigo (2023)
The aim of this paper is to analyze the Brazilian industry innovation pattern, considering the Pavitt Taxonomy. The hypothesis is the Pavitt Taxonomy does not work with development countries. To test this hypothesis this paper has used PINTEC database complemented with RAIS and PIA databases. The methodological framework was Factorial Analysis to find relevant factors combined with Cluster Analysis to create sectorial groups with the same technological change characteristics. The factors created (innovation impact, innovation expenditures, knowledge appropriation and industrial projects and marketing expending) have been good enough to detect sectorial patterns of innovation in the Brazilian industry. The paper contributes to showing that size firm is not a good variable to investigate sectorial pattern in Brazilian industry. The Brazilian industry presents some convergence with Pavitt taxonomy but presents some specificities confirmed by previous studies.